Проблеми вдосконалення концептуальних засад права власності на природні об'єкти а їх ресурси у конституційному вимірі - Каракаш, Ілля Іванович; Каракаш, Илья Иванович; Karakash, Il'ja (My University, 2013)
The article reveals the methodological foundations consolidate ownership of natural objects and their resources in the Constitution of Ukraine currently considered modern looks to consolidate ownership of natural resources and the proposed transition to their constitutional recognition on the basis of national heritage and national identity.
Каракаш І. І. Проблеми вдосконалення концептуальних засад права власності на природні об'єкти а їх ресурси у конституційному вимірі / І. І. Каракаш// Наукові праці Національного університету «Одеська юридична академія» : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.), Ю. П. Аленін [та ін.] ; відпов. за вип. В. М. Дрьомін ; МОН України, НУ ОЮА. – Одеса : Юрид. л-ра, 2013. – Т. 13. – С. 283-292.
Keywords: Конституція; конституційний акт; право власності; природні багатства; приодні об'єкти; природні ресурси; народне надбання; народна приналежність; Конституция; конституционный акт; право собственности; природные объекты; природные ресурсы; народное достояние; народная принадлежность; Constitution; constitutional act; the right to property; natural resources; natural features; natural resources; national heritage; national identity